Impact evaluation of a maternal and neonatal health training intervention in private Ugandan facilities. Issue 7 (29th June 2021) - Baumgartner, Joy Noel; Headley, Jennifer; Kirya, Julius; Guenther, Josh; Kaggwa, James; Kim, Min Kyung; Aldridge, Luke; Weiland, Stefanie; Egger, Joseph
Abstract: Global and country-specific targets for reductions in maternal and neonatal mortality in low-resource settings will not be achieved without improvements in the quality of care for optimal facility-based obstetric and newborn care. This global call includes the private sector, which is increasingly serving low-resource pregnant women. The primary aim of this study was to estimate the impact of a clinical and management-training programme delivered by a non-governmental organization [LifeNet International] that partners with clinics on adherence to global standards of clinical quality during labour and delivery in rural Uganda. The secondary aim included describing the effect of the LifeNet training on pre-discharge neonatal and maternal mortality. The LifeNet programme delivered maternal and neonatal clinical trainings over a 10-month period in 2017–18. Direct clinical observations of obstetric deliveries were conducted at baseline ( n = 263 pre-intervention) and endline ( n = 321 post-intervention) for six faith-based, not-for-profit primary healthcare facilities in the greater Masaka area of Uganda. Direct observation comprised the entire delivery process, from initial client assessment to discharge, and included emergency management (e.g. postpartum haemorrhage and neonatal resuscitation). Data were supplemented by daily facility-based assessments of infrastructure during the study periods. Results showed positive and clinically meaningful increases in observed handwashing, observed delayed cord clamping, partograph use documentation and observed 1- and/or 5-minute APGAR assessments (rapid scoring system for assessing clinical status of newborn), in particular, between baseline and endline. High-quality intrapartum facility-based care is critical for reducing maternal and early neonatal mortality, and this evaluation of the LifeNet intervention indicates that their clinical training programme improved the practice of quality maternal and neonatal healthcare at all six primary care clinics in Uganda, at least over a relatively short-term period. However, for several of these quality indicators, the adherence rates, although improved, were still far from 100% and could benefit from further improvement via refresher trainings and/or a closer examination of the barriers to adherence.